Openstreetmap Application For Mobile Devices That Tracks Customer Service Coordinates - Hendharsetiawan, Andy Achmad; Khaerudin, Muhammad (Moneter: Jurnal Keuangan dan Perbankan, 2024)
One of the most recent innovations in customer service, where competition is fierce, is mapping consumer coordinates. Given that the clientele is dispersed among multiple villages and sub-districts. Consumer place mapping is not without its challenges. Finding data sources can be challenging in and of itself, aside from regional problems and a staffing deficit. to build a customer service system by using facilities. OpenStreetMap (OSM) was then built using an HTML website framework, MySQL with Myadmin PHP features, and the OpenStreetMap API. OpenStreetMap (OSM) is a mapping tool that enables exact mapping of virtually all of Indonesia's residential areas through the use of satellite photography. Furthermore, by dividing the mapping region into smaller mapping pieces, the tasking manager tool in OSM speeds up digitizing. This makes it possible for several OSM volunteers to map the same region concurrently across several districts or cities. in Indonesia